2001
DOI: 10.1088/0022-3727/34/24/102
|View full text |Cite
|
Sign up to set email alerts
|

Swarm parameters in SF6and CO2gas mixtures

Abstract: In this article, we present an analysis of the avalanche growth in electronegative gases, including detachment as well as ionization and attachment processes. The model is used to determine swarm parameters from a pulsed Townsend discharge. As an example, the swarm parameters for SF6-CO2 of electron ionization, attachment and detachment coefficients have been determined. The value of transport coefficient for SF6-CO2 has also been given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…In the absence of any other R net measurements in SF 6 , to our knowledge 16 , figure 4 only displays the rate coefficient of Aschwanden [66], reported directly in that thesis, and the rate coefficients of de Urquijo et al [103] and Xiao et al [98,104], transformed through the relationship (30), with good agreement observed between all.…”
Section: Sfmentioning
confidence: 93%
“…In the absence of any other R net measurements in SF 6 , to our knowledge 16 , figure 4 only displays the rate coefficient of Aschwanden [66], reported directly in that thesis, and the rate coefficients of de Urquijo et al [103] and Xiao et al [98,104], transformed through the relationship (30), with good agreement observed between all.…”
Section: Sfmentioning
confidence: 93%
“…The swarm data of C 3 F 7 CN have also shown that the effective ionisation coefficient increases much slower with increasing electric field than that of SF 6 . The slopes of C 3 F 7 CN and SF 6 gases are 3.53 � 10 −24 and 3.04 � 10 −23 m 2 /Td, respectively [24,25]. This means that less energy is required for to ionise C 3 F 7 CN than SF 6 .…”
Section: Surface Roughness Measurementsmentioning
confidence: 98%
“…where σ m is the total momentum cross-section consisting of contributions from all possible collision processes. Several papers [40][41][42] have given the measurement result for μ e N at 300 K. In Fig. A6, μ e N values measured at 300 K are denoted by several symbols such as open circles.…”
Section: Rate Coefficient For Electron Collision Process In Hot Sf 6 Gasmentioning
confidence: 99%